Khamr in the Perspective of Maslahah Mursalah: A Balance Between Goodness and Legislation on the Prohibition of Alcoholic Beverages - Nanda Purnama; Arlangga surya Renata; Batara Wahyu Putera; Bobo Alex Sandro; Muhammad Hafiizh Nurhuda (Westscience Press, 2023)
The law regarding alcoholic beverages in Indonesia is still a polemic, for example there is MUI Fatwa No. 11 of 2019 concerning Laws related to Alcohol, unfortunately it is not legally binding and only applies to Muslims in Indonesia. Laws banning alcoholic beverages must be passed in order to enforce laws that apply to everyone, given the current situation, it is important for Indonesia to introduce rules banning alcoholic beverages to ensure that the public is always aware of the dangers they pose. The dangers posed by alcoholic beverages are discussed in this qualitative literature study (library research) from a philosophical and historical perspective using the maqasid al-shari'ah approach. The objectives of the maqasid al-shari'ah study of the prohibition of alcohol and the prohibition of khamr are to: First, Take advantage and eliminate mudharat, Next, the pattern Second, the purpose of saad al-Dzari'ah is to uphold the principle of dar'ul mafasidi muqaddamun 'ala jalbil mashalih, which states that doing good is more important than doing harm. This is done to preserve property, fate, soul, and reason. This shows that all harmful drinks, including khamr, are prohibited and hence considered haram because they use the same legal 'illat as khamr.